Atmospheric and Biological Environmental Monitoring - Kim, Young J.; Platt, Ulrich.; Gu, Man Bock.; Iwahashi, Hitoshi. (Springer Netherlands, 2009)
The harmful impacts of pollution on atmospheric, terrestrial and aquatic environments can cause extreme temperature changes, clean water shortage, and increase toxicity. This book studies environmental pollution impacts, from the mechanism of toxic nanoparticles on the molecular level to the detection of trace gas on the satellite perspective. It presents recent developments in advanced monitoring techniques, efficient process technologies and health impact assessment tools, from environmental scientists of diversified fields. The three sections highlight important aspects of emerging monitoring technologies in Atmospheric Environment, Contaminants Control Process and Environmental Toxicity Assessment. Observational tools presented in the first section range from in-situ analytical to digital techniques for atmospheric monitoring. Highlighted in the second section is the recently developed water quality monitoring system for lake stratification and membrane technologies for detection and removal of contaminants. Lastly, toxicity mechanisms of endocrine disruptors and nanoparticles are highlighted on the third section, with important new discoveries. The major topics addressed are: atmospheric environmental monitoring, including monitoring and modeling of trace air pollutants, contaminants control process monitoring, environmental toxicity monitoring and assessments, biological and chemical monitoring for environmental toxicity, monitoring technology for desalination water quality and toxicity measurement of desalted and concentrated water.